'Neoavanguardia' : Italian Experimental Literature and Arts in the 1960s - Chirumbolo, Paolo; Somigli, Luca; Moroni, Mario, 1955- (Book collections on Project MUSE., 2010)
"The Italian neoavanguardia, a literary and artistic movement characterized by a strong push towards experimentation, playfulness, and new forms of language usage, was founded at the beginning of the 1960s by a group of poets, critics, artists, and composers. Although the neoavanguardia movement has been primarily defined and examined in a literary context, it is broadly discussed in this collection as also affecting other artistic forms such as the visual arts, music, and architecture.